Description of a nomen nudum species of Liriomyza Mik and the first record of Liriomyza blechi Spencer from Brazil (Insecta: Diptera: Agromyzidae) - Carvalho-Filho, Fernando Da Silva; Almeida, Flávio Roberto De Albuquerque; Esposito, Maria Cristina (Zootaxa, 2016)
The nomen nudum Liriomyza flagellae is formerly described in this paper as Liriomyza valladaresae sp. nov., based on male and female specimens collected in the Brazilian Amazon and reared from leaves of Alternanthera tenella and Amaranthus viridis (Amaranthaceae). Information on the puparium and the biology of this new species are provided. The species Liriomyza blechi, previously recorded from the U.S.A., Guadeloupe and Dominican Republic, is newly recorded from Brazil, reared from leaves of Blechum pyramidatum (Acanthaceae) and Spigelia anthelmia (Loganiaceae).